Cultural tightness and scientific capacity: A cross-national study of their synergistic and conflicting roles in COVID-19 pandemic outcomes - Chris William Callaghan (PLoS ONE, 2026)
Despite their advanced scientific capacity, many nations experienced high COVID-19 cases and deaths during the pre-vaccine phase of the pandemic. In contrast, some countries with tighter cultural norms, where social behaviour is more strongly regulated, appear to have controlled the spread of the virus more effectively. This creates a paradox: the same norm strength that may support compliance with public-health measures may also be less conducive to ideation, creativity, and scientific output. While prior research has associated cultural tightness with lower COVID-19 cases and deaths, its relationship with scientific capacity remains underexplored. This study examines associations between scientific capacity, cultural tightness, and COVID-19 outcomes using cross-national data. Findings show that scientific capacity has no robust direct protective association with pre-vaccine COVID-19 cases or deaths once cultural tightness and structural covariates are included. In contrast, Gelfand’s measure of cultural tightness is consistently associated with lower cases and deaths. These findings suggest that scientific knowledge alone does not automatically translate into population-level protection, and that norm strength, behavioural coordination, and knowledge-to-action capacity may be important conditions of pandemic resilience.